An attitude approach to the prediction of entrepreneurship on students at institution of higher learning in Malaysia - Mohd Shariff, Mohd Noor; Saud, Mohammad Basir (Canadian Center of Science and Education, 2009)
An attitude approach to the prediction of entrepreneurship has been the subject of extensive research in the developed world.However, this approach especially entrepreneurship attitude among students in the institutions of higher learning has not been conducted extensively in Malaysia and is ripe for research. This paper reports the findings on the entrepreneurship attitude perspective of the final year business management undergraduate students in one of the Institutions of Higher Learning in Malaysia. Fifty-eight undergraduates minored in entrepreneurship courses and sixty-five non-minored undergraduates from the Faculty of Business Management were tested and validated using the Entrepreneurial Attitude Orientation (EAO) scale instrument.Discriminant validity was used to test the known groups. There was a significance difference between known groups for two of the four EAO subscales (self-esteem and personal control); all subscales were entered into a stepwise discriminant function.The classification results showed that the overall number of cases classified correctly was 104 or 84.6 percent of the sample.